Iqra' as Knowledge Paradigm: Islamic Epistemology Reconstruction from QS Al-Alaq 1-5 - Hartono, Hartono; Ismail (MAGHZA, 2026)
This study reconstructs Islamic epistemology by positioning the Qur'anic command "Iqra'" (recite/read) in QS Al-Alaq 1-5 as a central paradigm of knowledge. Employing hermeneutic analysis integrated with philosophical inquiry, this research demonstrates that "Iqra'" extends beyond textual literacy to encompass recognition of divine signs through revelation, intellect, and empirical experience. Three dimensions emerge: (1) revelation (naql) as the primary epistemological source; (2) an integrative knowledge process synthesizing revelation, reason, and observation of natural phenomena (ayat kauniyyah); and (3) transcendental knowledge aims directed toward ma'rifah—intimate recognition of the Divine—and alignment with Islamic ethical values. This holistic epistemology offers a robust alternative to Western reductionist paradigms by integrating material, intellectual, and spiritual dimensions of knowledge production. The paradigm demonstrates particular relevance for contemporary Islamic education reform, ethical frameworks in science and technology, and substantive intercultural dialogue on epistemological foundations. The study contributes an original framework through systematic integration of classical tafsir scholarship with contemporary epistemological analysis, positioning "Iqra'" not merely as a historical narrative but as a foundational epistemic principle for twenty-first-century knowledge systems. The implications extend across educational policy, scientific ethics, and global intellectual exchange.